Protective Effect of Hydroxygenkwanin against Hair Graying Induced by X-Ray Irradiation and Repetitive Plucking - Nobuhiko Taguchi; Ryosuke Kitai; Takuya Ando; Toshihiro Nishimura; Hitomi Aoki; Takahiro Kunisada (Elsevier, 2022)
Hair graying in mice is caused by various injuries such as X-ray radiation and repeated plucking that ultimately damage melanocytes and their stem cells (melanocyte stem cells). In X-ray‒induced hair graying, injuries first manifest as a loss-of-niche function of hair follicular keratinocyte stem cells to maintain melanocyte stem cells. Thus, we hypothesized that hair follicular keratinocyte stem cells could be a practical target to prevent hair graying. In this study, we investigated the in vivo effect of the flavonoid hydroxygenkwanin, which has been shown to exert the best protection on human epidermal keratinocytes against in vitro X-ray‒induced cytological effects, using X-ray‒induced and repeated hair plucking‒induced hair graying mice models. We found that hydroxygenkwanin exerted a remarkable effect in preventing hair graying; however, when receptor Y kinase Kit-mutant mice were used, no prevention effect was observed. Therefore, we propose that Kit signaling might be involved in the hydroxygenkwanin-induced protective effect against hair graying.